Fabrication of highly sensitive and uniform Ag/PS/PDMS SERS substrate and its application for in-situ detection. (11th June 2022) - Xu, Guangming; Shen, Xilong; Zhang, Lei; Tang, Jie; He, Chuan; Zhou, Ziqiang; Xu, Tian; Xu, Meifeng; Jin, Yonglong; Wang, Chaonan
Abstract: In this study, we developed a flexible and transparent silver/polystyrene/polydimethylsiloxane (Ag/PS/PDMS) substrate with both high density of hot spots and satisfactory uniformity using a cost-effective approach. Via template-guided self-assembly, PS beads were arranged regularly in nanobowls of a square array on PDMS, whose surface structure was transferred from a commercial complementary metal oxide semiconductor chip. Roughness was introduced onto the PS bead surface by nitrogen plasma treatment, followed by sputtering of Ag which generated many hot spots. Differential roughness on the PS bead surface greatly influenced the morphology of the Ag/PS/PDMS substrate. A meat-ball like surface structure was formed with a plasma etching time of 5 min, whose growth mechanism was proposed based on the scanning electron microscope analysis. The high sensitivity and desirable uniformity of the meat-ball like Ag/PS/PDMS substrate were demonstrated by using crystal violet as a Raman reporter, exhibiting an enhancement factor of 2.7 × 10 7 and a relative standard deviation of 5.04%. Thiram of a lower concentration than the maximum residue limit on the cucumber surface could easily be detected in situ by the proposed substrate, demonstrating its great potential for in-situ food safety analysis.